Competing and contested discourses of citizenship and civic praxis - Jill Koyama (Arizona State University, 2017)
In this paper, I utilize complementary features of critical discourse analysis (CDA) and Actor-Network Theory (ANT) to trace and investigate issues of power, materiality, and reproduction embedded within notions of citizenship and civic engagement. I interrogate the often narrow and conservative political and public discourses in Arizona, as well as the xenophobic-driven civics education policy. To these, I juxtapose the enactment of citizenship by youth who use, produce, and share language materials and counter authoritative citizenship and civic discourses, especially, but not exclusively, in online contexts.  I explore the questions: In what ways are discourses of civic engagement and citizenship assembled, interpreted, understood, enacted, and contested in Arizona? What are the relationships between the civics education policy, discursive enactments of citizenship, and the youth of Mexican descent's online civic practices? I draw on a mixture of textual (language materials) and discursive (events, acts, and practices) data collected in Arizona to argue that youth are doing critical, yet unrecognized and undervalued, forms of civic engagement online, which could be incorporated in the formal civics education curriculum.